A brief update on the evidence supporting the treatment of infertility in polycystic ovary syndrome. (12th September 2019) - Costello, Michael F.; Misso, Marie L.; Balen, Adam; Boyle, Jacqueline; Devoto, Luigi; Garad, Rhonda M.; Hart, Roger; Johnson, Louise; Jordan, Cailin; Legro, Richard S.; Norman, Rob J.; Moran, Lisa; et al.
Abstract : Background: Polycystic ovary syndrome (PCOS) is complex with reproductive, metabolic and psychological features. Infertility is a prevalent presenting feature of PCOS with approximately 75% of these women suffering infertility due to anovulation, making PCOS by far the most common cause of anovulatory infertility. Previous guidelines either lacked rigorous evidence‐based processes, did not engage consumer and international multidisciplinary perspectives, or were outdated. Aims: This review paper aims to provide a brief update on the best available and most current research evidence supporting the treatment of PCOS which informed the recommendations in the assessment and treatment of infertility section of the international evidence‐based guideline on PCOS 2018. Materials and Methods: International evidence‐based guideline development engaged professional societies and consumer organisations with multidisciplinary experts and women with PCOS directly involved at all stages. Results: Lifestyle change alone is considered the first‐line treatment for the management of infertile anovulatory PCOS women who are overweight or obese. Letrozole should now be considered first‐line pharmacological treatment for ovulation induction to improve fertility outcomes. Clomiphene citrate alone and metformin alone could also be used as first‐line pharmacological therapy, although both are less effective than letrozole and metformin is less effective than clomiphene citrate in obese women. Gonadotrophins or laparoscopic ovarian surgery are usually second‐line ovulation induction therapies. In the absence of an absolute indication for in vitro fertilisation (IVF) / intracytoplasmic sperm injection, women with PCOS and anovulatory infertility could be offered IVF as third‐line therapy where first‐ or second‐line ovulation induction therapies have failed. Conclusion: This review provides the best available evidence informing recommendations (along with clinical expertise and consumer preference) which provide clinicians with clear advice on best practice for the management of infertile women with PCOS.